Identification of Warning Signs in Aging Neglected self-care - Bana , Cesar Augusto (Seven Editora, 2023)
The increase in elderly population is constantly growing, at the same time that life expectancy has also increased, providing many reflections and studies on the subject of aging. Until recently, the view of old age was stereotyped, seeing aspects related to loss, uselessness, and loneliness. However, this view is changing, the elderly represent 12% of the world's population, with a forecast to double this amount by 2050 and triple by 2100. The process of inverting the age pyramid, associated with increased longevity, results in greater relevance of the family in the context of care for the elderly, since the family assumes the role of care, leading to changes in the family context. According to Aguiar, Menezes, and Camargo (2017), in about 3.2 million elderly people, it is the family that plays the role of care. DOI:https://doi.org/10.56238/devopinterscie-158